Comparison of a 4-Day versus 2-Day Low Fiber Diet Regimen in Barium Tagging CT Colonography in Incomplete Colonoscopy Patients - Kaan Meric; Nuray Bakal; Ebubekir Şenateş; Sibel Aydın; Zeynep Gamze Kılıçoğlu; Fatma Esra Bahadır Ülger; Esin Yencilek; Banu Erkalma Şenateş; Masum Şimşek (Gastroenterology Research and Practice)
Our aim was to compare the amount of residual feces, residual fluid, the tagging quality, and patient compliance using 4-day versus 2-day low fiber diet regimen in barium tagging CT colonography in incomplete colonoscopy patients. Methods. A total of 101 patients who underwent CT colonography were assigned to 2-day diet group (n=56) and 4-day diet group (n=45). Fecal tagging was achieved with barium sulphate while bisacodyl and sennoside B were used for bowel preparation. Residual solid stool was divided into two groups measuring <6 mm and ≥6 mm. We graded the residual fluid, tagging quality for solid stool, and fluid per bowel segment. We performed a questionnaire to assess patient compliance. Results. 604 bowel segments were evaluated. There was no significant difference between 2-day and 4-day diet groups with respect to residual solid stool, residual fluid, tagging quality for stool, and fluid observed in fecal tag CT colonography (P>0.05). The prevalence of moderate discomfort was significantly higher in 4-day group (P<0.001). Conclusion. Our study shows that 2-day limited bowel preparation regimen for fecal tag CT colonography is a safe and reasonable technique to evaluate the entire colon, particularly in incomplete conventional colonoscopy patients.